Determinan Pemahaman Akuntansi Selama Pandemi Covid-19 - Ni Made Ayu Genitri; Jurana Jurana; Muhammad Ilham Pakkawaru (Universitas Muhammadiyah Jakarta, 2023)
Covid-19 as a global pandemic demands a change in the learning process to be carried out online. This change is expected to impact the level of understanding for students, including college students. This study aims to empirically examine it on accounting students during the pandemic. With quantitative method based on primary data, the population is the students of Tadulako University. And with nonprobability sampling technique, 79 samples were established. This study employs multiple linear regression. The results show that learning behavior, academic intelligence, and spiritual intelligence have significant positive impact on the level of understanding of accounting students both simultaneously and partially during the pandemic